(untitled) (LACCEI, 2024)
Abstract– The objective of the research was to determine the relationship of gender equity with job satisfaction in the employees of the El Rancho de Jara Beef restaurant, Trujillo 2022. The research was developed with a non-experimental design, quantitative approach, correlational scope, working with a questionnaire prepared with a likert scale, whose level of reliability for the gender equity variable is 0.933 and job satisfaction of 0.929. The correlation of both variables amounts to 0.853 in the Rho Spearman.